Ethical issues in scientific publications - Job, Ivone (2011)
This work discuss the ethical issue in the scientific and academic production, analizes situations which the conflict comes in the scientific comunities midst the actors and echoes in the whole way to research nowadays. It is mentioned examples found in the literature into different aspects considered misconduct: plagiarism, fabrication or falsification of data, nonpublication of data, authoring problems and issues related to copyright  and misconduct commited by journal referees/ editors. At the end, considerations are made about the subject, among them, that the topic is still not discussed between the students, teachers, in the school and society in general and, if so, several cases would be avoided certainly.